PROBIOTICS AS AN ADJUNCTIVE THERAPY FOR CELIAC DISEASE: SYMPTOM RELIEF AND QUALITY OF LIFE IMPROVEMENT - Gabriel Fernandes Alves JESUS; Monique MICHELS; Emily CÓRNEO; Marina P ROSSETTO; Alexandre J FARACO; Ana Paula PESARICO (Arquivos de Gastroenterologia, 2025)
ABSTRACT Background: Celiac disease is a chronic autoimmune disorder triggered by gluten ingestion in genetically predisposed individuals, leading to intestinal damage. Probiotics have been studied for their potential benefits in modulating gut microbiota and alleviating gastrointestinal symptoms, which may be beneficial in managing celiac disease (CD). Objective: In this way, this study evaluated the effects of probiotics compared to placebo in individuals with CD over the course of treatment. Methods: A total of 85 participants, with an average age of 40 years, were randomized into two groups using a computer-generated list: 39 receiving placebo and 46 receiving a probiotic blend of Bifidobacterium lactis CCT 7858 and Lactobacillus rhamnosus CCT 7863 (1 x 109 CFU/day) over 90 days. Participants received either a daily probiotic capsule or an identical placebo made from maltodextrin, provided by Gabbia Biotecnologia Ltda. The randomization process and group assignments were concealed from both participants and investigators. Results: Both groups exhibited similar demographic and clinical characteristics, with most participants symptomatic for CD and adhering to a gluten-free diet. The Bristol Stool Form Scale (BSFS) showed a predominance of normal stool forms in both groups, with a higher prevalence of type 4 in the probiotic group. Gastrointestinal Symptom Rating Scale (GSRS) scores improved significantly in the probiotic group compared to placebo. Additionally, the probiotic group showed significant improvements in emotional well-being and gastrointestinal symptoms, leading to a better quality of life, as measured by the CD-specific quality of life (CD-QOL) scores. Conclusion: These results suggest that probiotics contribute to symptom improvement and enhanced quality of life in CD patients.